Handbook of frozen food processing and packaging / Da-Wen Sun - Sun, Da-Weneditor
This book •Discusses quality and safety issues for each frozen food category in individual chapters, ensuring comprehensive coverage •Covers fundamental aspects of freezing such as glass transition, microbiology of frozen foods, thermophysical properties, and freezing process modeling •Examines freezing and packaging equipment, transportation methods and facilities, and cold chain monitoring techniques